2008
DOI: 10.1111/j.1464-410x.2008.07775.x
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility and safety of high‐intensity focused ultrasound as salvage therapy for recurrent prostate cancer following external beam radiotherapy

Abstract: OBJECTIVES To investigate the use of minimally invasive high‐intensity focused ultrasound (HIFU) as a salvage therapy in men with localized prostate cancer recurrence following external beam radiotherapy (EBRT). PATIENTS AND METHODS A review of 31 cases treated using the Sonablate® 500 HIFU device, between 1 February 2005 and 15 May 2007, was carried out. All men had presumed organ‐confined, histologically confirmed recurrent prostate adenocarcinoma following EBRT. RESULTS The mean (range) age was 65 (57–80) y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 23 publications
0
66
2
Order By: Relevance
“…Our results suggest that DCE may be easy for radiologists to interpret (81.1% agreement), though its relative low PPV (64.9%) suggests that metallic seed distortion may limit its interpretation. It is possible that the discrepancy between our findings and others resulted from a more heterogeneous decrease in prostate vascularization after brachytherapy compared with EBRT, making it more difficult to interpret post-brachytherapy DCE (22).…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Our results suggest that DCE may be easy for radiologists to interpret (81.1% agreement), though its relative low PPV (64.9%) suggests that metallic seed distortion may limit its interpretation. It is possible that the discrepancy between our findings and others resulted from a more heterogeneous decrease in prostate vascularization after brachytherapy compared with EBRT, making it more difficult to interpret post-brachytherapy DCE (22).…”
Section: Discussioncontrasting
confidence: 94%
“…Other studies have examined mpMRI efficacy after EBRT (19)(20)(21)(22), and observed DCE to be a valuable sequence. Our results suggest that DCE may be easy for radiologists to interpret (81.1% agreement), though its relative low PPV (64.9%) suggests that metallic seed distortion may limit its interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the rates of genitourinary and pelvic complications appear to be encouragingly low. 8 One of the major challenges in selecting men who are suitable for salvage therapy is accurate staging. It is estimated that up to 50% of men who fail EBRT may have distant metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…The biochemical cancer control rates that result from these salvage therapies are on the order of 40% to 60% over 2 to 5 years follow-up. [6][7][8] We previously reported our early results using focal therapy in men with primary disease. 9 Focal salvage therapy has been proposed as an alternative that may provide treatment for localized, radiorecurrent disease while reducing the impact on functional status.…”
Section: Introductionmentioning
confidence: 99%
“…3 Its advantages are manifold according to the investigator centres: it is minimally invasive, it can be repeated if required and other treatments can be offered in cases of incomplete treatment or recurrence. 4,5 Currently, it is used in patients who are not eligible for surgery or as salvage therapy for local recurrence after radiotherapy. Patients are often informed that the treatment is local and precise, can be repeated, requires a short hospital stay and is associated with few side effects.…”
Section: Introductionmentioning
confidence: 99%